2014
DOI: 10.1111/1469-0691.12703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prompt catheter withdrawal and adequate antimicrobial therapy on the prognosis of hospital-acquired parenteral nutrition catheter-related bacteraemia

Abstract: Catheter-related bacteraemia (CRB) is a cause of death in hospitalized patients, and parenteral nutrition (PN) is a risk factor. We aim to describe the prognosis of PN-CRB and the impact of catheter extraction within 48 h from bacteraemia. All consecutive hospitalized adult patients with CRB (2007-2012) were prospectively enrolled. Factors associated with 30-day mortality were determined by logistic regression analysis. Among 847 episodes of CRB identified, 291 (34%) episodes were associated with short-term ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Twenty‐one full‐text articles were retrieved. Ten 23 32 were excluded as they did not meet the inclusion criteria (see Figure 1). Eleven studies were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐one full‐text articles were retrieved. Ten 23 32 were excluded as they did not meet the inclusion criteria (see Figure 1). Eleven studies were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This supports the theory that the administration of PN alone may not inherently hold additional risk for the development of CRBSIs. Alonso‐Echanove et al 45 and Rodriguez‐Pardo et al 32 found that the distribution of pathogens was influenced by PN. Fungi and yeasts were isolated more frequently when PN was prescribed (16% vs 6%; P = .01).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, experts agree that, as a general rule, the catheter should be removed whenever these microorganisms are involved, limiting attempts salvage the catheter to patients with selected difficult circumstances [1,2,10]. In the case of CoNS, although retaining the catheter is also associated with a higher incidence of persistent bacteraemia and relapse [24,25], removing an involved central venous catheter in patients without intravascular hardware is less compelling as the response rate to systemic antibiotics alone in adults is 80% [26] and the frequency of complications and attributable mortality is very low [27].…”
Section: Discussionmentioning
confidence: 99%
“…In catheter-bearing patients with bacteraemia without an obvious focus, pre-test probabilities of the catheter being the source of infection are probably high enough to consider the removal of the device in all cases. Prevalence of CRBSI in patients with S. aureus or enterococcal bacteraemia who carry a catheter or acquire the infection in the hospital is expected to be at least onethird [13,23,28] and figures not lower than 25% are also expected for Gram-negative bacilli, Candida and CoNS [21,24,25]. Therefore, a test allowing CRBSI to be ruled out with a high degree of confidence would be particularly valuable.…”
Section: Discussionmentioning
confidence: 99%